LSD1 mediates MYCN control of epithelial-mesenchymal transition through silencing of metastatic suppressor NDRG1 gene - Susanna Ambrosio; Stefano Amente; Carmen Daniela Saccà; Mario Capasso; Raffaele Calogero; Luigi Lania; Barbara Majello (2016)
// Susanna Ambrosio 1 , Stefano Amente 2 , Carmen D. Saccà 1 , Mario Capasso 2,3 , Raffaele A. Calogero 4 , Luigi Lania 2 and Barbara Majello 1 1 Department of Biology, University of Naples 'Federico II', Naples, Italy 2 Department of Molecular Medicine and Medical Biotechnologies, University of Naples, 'Federico II', Naples, Italy 3 CEINGE Biotecnologie Avanzate, Napoli, Italy 4 Molecular Biotechnology Center, Department of Molecular Biotechnology and Health Sciences, University of Torino, Turin, Italy Correspondence to: Barbara Majello, email: // Keywords : MYCN; LSD1; NDRG1; EMT; neuroblastoma Received : July 20, 2016 Accepted : October 14, 2016 Published : November 22, 2016 Abstract Neuroblastoma (NB) with MYCN amplification is a highly aggressive and metastatic tumor in children. The high recurrence rate and resistance of NB cells to drugs urgently demands a better therapy for this disease. We have recently found that MYCN interacts with the lysine-specific demethylase 1 (LSD1), a histone modifier that participates in key aspects of gene transcription. In cancer cells, LSD1 contributes to the genetic reprogramming that underlies to Epithelial-Mesenchymal Transition (EMT) and tumor metastasis. Here, we show that LSD1 affects motility and invasiveness of NB cells by modulating the transcription of the metastasis suppressor NDRG1 (N-Myc Downstream-Regulated Gene 1). At mechanistic level, we found that LSD1 co-localizes with MYCN at the promoter region of the NDRG1 gene and inhibits its expression. Pharmacological inhibition of LSD1 relieves repression of NDRG1 by MYCN and affects motility and invasiveness of NB cells. These effects were reversed by overexpressing NDRG1. In NB tissues, high levels of LSD1 correlate with low levels of NDRG1 and reduced patients survival. Collectively, our findings elucidate a mechanism of how MYCN/LSD1 control motility and invasiveness of NB cells through transcription regulation of NDRG1 expression and suggest that pharmacological targeting of LSD1 represents a valuable approach for NB therapy.